Article Review - Recent Advances in Hepatitis C Virus: Therapy and Diagnosis - Al-ma’amouri, May Y. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Hepatitis C virus (HCV) is one of the major causes of chronic liver disease worldwide. Significant progress has been made in both diagnosis and treatment over recent years. Modern serological and molecular tests now enable early detection of the virus, allowing timely and effective treatment. Direct-acting antivirals (DAAs) have revolutionized therapy, achieving cure rates exceeding 95% with minimal side effects. This paper reviews the etiology, epidemiology, pathophysiology, clinical stages, diagnostic advancements, treatment options, preventive strategies, and future directions in the fight against Hepatitis C.